Medical genetics and genomics : questions for board review - Solomon, Benjamin D. (Hoboken, NJ : Wiley-Blackwell, 2023)
"Physician and genetic counsellor trainees are required to take 'board examinations' for accreditation/ongoing certification in the various fields of medical genetics and genomics. These examinations are typically taken at the end of training, and are often required at recurring intervals. This book is intended to help readers prepare for these tests, as well as to enable ongoing learning that may be of interest for active practitioners. The field of medical genetics and genomics is a rapidly growing area of medicine worldwide. To help clinicians and related laboratory experts learn about and stay current in this field, we have assembled a set of hundreds of questions and annotated answers. These questions are designed for trainees and lifelong learners including in the fields of clinical genetics and genomics and genetic counselling who are preparing for advanced boards examinations and who otherwise want to review key concepts, definitions, and frequently encountered genetic conditions related to the field. Dr Solomon has been teaching formal classes at the National Institutes of Health (NIH) for over a decade. These classes are intended for physicians, laboratory geneticists, genetic counsellors, and related clinical trainees in the various fields of clinical genetics and genomics. He realized that that there are not question books in this field that can be used for preparation for the required examinations for accreditation. There are some online resources and some home-made sets of questions that may be informally shared, but there is a dearth of resources that allow preparation for end-stage board examinations for these specialties. He has put together a set of questions to address this need, which he uses in some of my board-review courses. He is frequently asked to share these questions with trainees, but felt that a more formal venue (a print book) would reach a much wider audience" --
Basics and Terminology -- Physical Examination -- Clinical Diagnosis and Manifestations of Specific Conditions -- Causes of Genetic Conditions and Laboratory and Testing Approaches -- Management of Genetic Conditions and Therapeutics -- Inheritance, Risk, and Related Calculations
BIBINDX
Keywords: Genomics; Genomics; Genetics; Electronic books; Examination Questions